Norovirus and rotavirus in surface, malacoculture, and human consumption water in Santa Catarina State, Brazil. (23rd December 2022) - Mortari, Andreza; Kolling, Deise; Sobral, Doris; Kist, Airton; De Dea Lindner, Juliano; Fongaro, Gislaine; Miotto, Marília
Abstract: This study evaluated the results recorded at the Central Public Health Laboratory of Santa Catarina state (Brazil) concerning the investigation of Rotavirus (RVA) and Norovirus (NoVs) – genogroups GI and GII. Samples were taken from seawater, river water, estuary water, lagoon water, and treated water samples, from 2018 to 2021. The aim was to correlate them with each other and evaluate their association with the type of water, presence of shellfish farming, population density, and sewage treatment. The most prevalent enteric virus was RVA, followed by NoV GI and NoV GII. There was a strong correlation between the presence/absence of RVA and the presence/absence of at least one NoV genogroup, mainly in samples collected in rivers. No correlation was observed between the presence of any virus and the presence of shellfish farming. When evaluating the binomial sewage treatment vs. population density, the correlation coefficients between population density and the presence of the virus in a sample were higher than the coefficients between the percentage of treated sewage and the presence of the virus. Sources of human-origin pollution impair the quality of treated and surface waters, and therefore the results of this work can help develop viral-monitoring programs in these places. HIGHLIGHTS: Rotavirus (RVA) and Norovirus GI and GII (NoVs) were present in 42 and 44% of the analyzed samples, respectively. The most prevalent virus was RVA (42.3%), followed by NoV GI (22.90%) and NoV GII (22.3%). No association was observed between the presence of RVA and NoVs and the presence of shellfish farming. An association between population density, treated sewage, and the presence of RVA and NoVs was observed.